Morphological and Quality Traits Performance of the Fruits of Wild Pomegranate (Punica granatum L.) in Himachal Pradesh - Singh, 0Thiyam Jefferson; Gupta, Tara (International Journal of Bio-resource and Stress Management, 2018)
Present investigations were carried out on wild pomegranate (Punica granatum L.) in three locations spread across two districts of Himachal Pradesh. The extent of genetic variability, heritability and genetic advance with respect to fruit morphology (i.e. fruit width, fruit length, fresh weight of fruit, fresh weight of rind, fresh seed weight with pulp and fresh seed weight without pulp and quality traits (i.e TSS, total sugar, reducing sugar, non-reducing sugar, acidity and ascorbic acid) in the fruits of fifteen wild pomegranate genotypes from Tatool, Narag and Daro Deohria were studied. Fruit width, length, fresh weight of fruit, fresh weight of rind, TSS, total sugar, reducing sugar, non-reducing sugar and ascorbic acid were recorded with high heritability. Thus, selection of progenies based on performance would be effective for these characters. All the parameters were positively and significantly correlated with each parameter. Fresh weight of seed with aril had highly significant and positive correlation with fruit width, fruit length, total sugar and reducing sugar. Therefore, emphasis should be given to these characters while selecting a genotype for enhancing yield and fruit size in pomegranate. On the basis of desirable parameters, best individuals will be selected and tree improvement programme can be taken up for further studies.